Aspects of the Monetary Transmission Mechanism Under Exchange Rate Targeting : The Case of France - Levy, Joaquim (IMF Working Papers; Working Paper ;, 1997)
This paper examines monetary transmission in France using the vector autoregression methodology. Interest rates are decomposed into external and domestic components, and a nonrecursive contemporaneous structure is used to identify the system. Innovations in the external component are found to have a significant impact on economic activity, while innovations in the domestic premium have a statistically negligible effect, suggesting that interest rate hikes in defense of the franc may have had a smaller impact on the economy than usually thought. The paper also discusses some implications of Economic and Monetary Union and provides evidence concerning the importance of the credit channel in France.